The Return of Capital Controls as Emergency Tools to Counter Financial Crises: Iceland’s Crisis and the Constraints Imposed by the EEA Agreement - VITERBO, Annamaria (2010)
Paper presented at the Society of International Economic Law (SIEL) Second Biennial Conference, Universitat de Barcelona, 8-10 July 2010. TABLE OF CONTENTS: 1. Introduction. - 2. The causes of Iceland's financial and economic crisis. - 3. Iceland's reaction to the crisis. - 4. The implications of Iceland's membership in the EEA for the design of its capital controls regulations. - 5. Final remarks